Risk factors for overweight and obesity, and changes in body mass index of Chinese adults in Shanghai - Gu Huilin; Zuo Yuhua; Jiang Shan; Lu Huijuan; Bao Yuqian; Jia Weiping; Hou Xuhong; Xiang Kunsan (BMC, 2008)
Abstract Background Over the past two decades, the prevalence of overweight or obesity has increased in China. The aims of this study were to firstly assess the baseline prevelences and the risk factors for overweight and obesity, and secondly to detect the changes of body mass index (BMI) over a follow-up period in Chinese adults in Shanghai. Methods The data set of a population-based longitudinal study was analyzed. Anthropometric and biochemical data were collected for 5364 subjects (aged 25-95 years) during a period of 1998-2001. Among those individuals, 3032 subjects were interviewed and reexamined at the second survey from 2003 to 2004. Then the standardized prevalences for overweight and obesity were calculated using baseline data; the possible contributing factors of overweight and obesity were detected using binary logistic regression analysis; and the changes of BMI were evaluated after an average of 3.6-year follow-up period. Results (1) According to the WHO standard and the Chinese standard, the sex- and age-standardized prevalences were 27.5% and 32.4% for overweight, and 3.7% and 9.1% for obesity, respectively. (2) The risks of overweight and obesity differed among different age groups. Family history of obesity increased the risk of overweight and obesity by about 1.2-fold for both genders. Current male smokers had a lower risk of overweight and obesity (OR = 0.76, p < 0.05) than nonsmokers. In contrast, current male drinkers had a higher risk of overweight and obesity (OR = 1.42, p < 0.05) than nondrinkers. Compared with low-educated women, medium- and high- educated women were at lower risk of overweight and obesity, and the corresponding ORs (95% CIs) were 0.64 (0.52-0.79) and 0.50(0.36-0.68), respectively. (3) The annual changes of BMI means ranged from an increase of 0.1 kg/m2 to a decrease of 0.2 kg/m2 (by genders and age groups). Meanwhile, the BMI increase was statistically significant in the 35-44 years age group, and the BMI decrease was significant above 65 years for both genders. Conclusion This study showed high prevalence of overweight and obesity in Shanghai metropolis populations. The risk factors of overweight and obesity were multifactorial and gender specific. After 3.6 years, BMI means changed slightly, BMI increased mainly in middle-aged individuals and decreased in old individuals.